BEHAVIOR OF MEMBERS MADE OF ROLLED ANGLE SECTIONS SUBJECTED TO ECCENTRIC COMPRESSION - GOMATOS, ILIAS (Σχολή Πολιτικών Μηχανικών, 2018)
Members made of hot rolled angle sections are widely used as compression members in lattice structures, such as communication towers in remote terrains, due to their simplified connectivity and the ease of transfer, which contribute to the facilitation of erection and to a more economic structure. Single angle members, due to their type of connection, are mainly loaded eccentrically. On this field, there is lack of experimental research and few studies on numerical approaches have been made. In addition the design expressions of EN1993-1-1 and EN1993-3-1 for angle cross-sections are based on other type of cross-sections, which leads to a conservative design. For filling the gaps on this field, this thesis is a numerical approach of experimental buckling tests on pinned angle members which took place in the Institute of Steel Structures of N.T.U.A., for evaluation of the experimental results. For the numerical approach, finite element method was used. The experimental buckling tests were simulated via both shell and solid finite element models. Initially a more geometrically precise solid finite element model was created, so that the simplified models could be evaluated as an adequate simulation, which were used for the analyses. The generated force-axial displacement, force-midspan deflection and force-midspan rotation curves were compared with the corresponding curves that were produced by the experimental tests, in order to be evaluated.